Saraf-dependent activation of mTORC1 regulates cardiac growth. (April 2020) - Sanlialp, Ayse; Schumacher, Dagmar; Kiper, Leon; Varma, Eshita; Riechert, Eva; Ho, Thanh Cao; Hofmann, Christoph; Kmietczyk, Vivien; Zimmermann, Frank; Dlugosz, Sascha; Wirth, Angela; Gorska, Agnieszka A.; et al.
Abstract: Pathological cardiac hypertrophy is an independent risk for heart failure (HF) and sudden death. Deciphering signaling pathways regulating intracellular Ca 2+ homeostasis that control adaptive and pathological cardiac growth may enable identification of novel therapeutic targets. The objective of the present study is to determine the role of the store-operated calcium entry-associated regulatory factor (Saraf), encoded by the Tmem66 gene, on cardiac growth control in vitro and in vivo . Saraf is a single-pass membrane protein located at the sarco/endoplasmic reticulum and regulates intracellular calcium homeostasis. We found that Saraf expression was upregulated in the hypertrophied myocardium and was sufficient for cell growth in response to neurohumoral stimulation. Increased Saraf expression caused cell growth, which was associated with dysregulation of calcium-dependent signaling and sarcoplasmic reticulum calcium content. In vivo, Saraf augmented cardiac myocyte growth in response to angiotensin II and resulted in increased cardiac remodeling together with worsened cardiac function. Mechanistically, Saraf activated mTORC1 (mechanistic target of rapamycin complex 1) and increased protein synthesis, while mTORC1 inhibition blunted Saraf-dependent cell growth. In contrast, the hearts of Saraf knockout mice and Saraf-deficient myocytes did not show any morphological or functional alterations after neurohumoral stimulation, but Saraf depletion resulted in worsened cardiac function after acute pressure overload. SARAF knockout blunted transverse aortic constriction cardiac myocyte hypertrophy and impaired cardiac function, demonstrating a role for SARAF in compensatory myocyte growth. Collectively, these results reveal a novel link between sarcoplasmic reticulum calcium homeostasis and mTORC1 activation that is regulated by Saraf. Highlights: Saraf expression is upregulated in hypertrophied myocardium and is sufficient for pathological cell growth in myocytes Saraf depletion results in deteriorated cardiac function after pressure overload Saraf activates mTORC1 signaling and protein synthesis in cardiac myocytes Saraf might link sarcoplasmic reticulum calcium homeostasis and mTORC1 activation during pathological growth